Developing Monitoring System Dashboard Module Using Iterative Incremental Method For Monitoring Ziswaf Productive Reporting Performance - Reicka Sofi Azura Ridhallah; Murahartawaty Murahartawaty; Ari Pratiwi (eProceedings of Engineering, 2016)
One of the problems that faced by Indonesia is the disparity (inequality) income distribution and poverty. In 2014 poor people in Indonesia reached 27.727,78 souls or 10,96%. The data is accompanied by an increase of unemployment in Indonesia. The concept of Zakat, Infak, Sodaqoh, and Waqf (ZISWAF) should be recognized by the government and all the people of Indonesia as one of the media in the realization of poverty reduction. Form of equitable distribution of income that can be one is to distribute the income of people who can afford to can not afford. One of the Islamic Financial institutions are tasked to collect the public fund and distribute them is Lembaga Amil Zakat (LAZ) or Badan Amil Zakat (BAZ). The existence of this institution aims at collecting funds from people who are afforded. ZISWAF potential in Indonesia in 2005 is estimated to reach Rp 19.3 trillion. Due percentage ZISWAF is an obligation for all Muslims able to or have reached ‘nisab’ in his property. Model portfolio ZISWAF by institutions there are two ways, namely consumtive and productive ways. In a productive way, with ZISWAF Fund processing includes planning, implementation, and coordination in the collection, distribution, and utilization of ZISWAF funds, Committed by both BAZ or LAZ. Other obstacles experienced by LAZ and BAZ in the distribution of funds to the poor is not very effective because the target is repeated or similar, is due to the absence of control within the data collection and reporting after the distribution of productive enterprise funds. The existence of the poor majority of the work on the micro business sector, the establishment of policies in providing funding productive activities is very influential with the hope to create new jobs and increase revenues. Based on the problem and to develop the Monitoring System that can help ZISWAF institutions in transparency to the public including the relevant parties. One of them is the Dashboard Micro Monitoring System, an application which is intended to establish Communications and interaction between the funders and built several Business sectors in an effort to increase its capacity in which the system functions to evaluate the distribution of fu nds reporting performance. Keywords: the poor in Indonesia, ZISWAF productive, LAZ and BAZ Institutes, Monitoring System.